A court of sugar and spice eaudiobook A nutcracker retelling. - Kenney, Rebecca F. (Wicked Darlings, 2023)
With their inheritance restricted until their marriage, sisters Clara and Louisa, both in their twenties, must live with their godfather Drosselmeyer. One night, an accident brings to life one of the strange wooden dolls in Drosselmeyer's mansion. The Nutcracker doll is a cursed Fae prince, and he pleads for the sisters' help. During the ensuing journey into the Fae realm, Clara encounters the handsome Sugarplum Faerie, and he promises her the chance to enact all her forbidden fantasies. Meanwhile Louisa and the Nutcracker Prince battle and bicker over everything, despite the growing attraction between them. And to make matters worse, the entire Seelie kingdom is under threat of conquest by the Rat King, ruler of the Dread Court. Contains mature themes. Trigger and content warnings are available on the author's website.